2022
DOI: 10.1155/2022/2566917
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Polygonatum cyrtonema Hua Reduce Depression-Like Behavior in Mice by Inhibiting Oxidative Stress-Calpain-1-NLRP3 Signaling Axis

Abstract: Polysaccharides from Polygonatum cyrtonema Hua (PSP) exert antioxidant, anti-inflammatory, and antidepressant effects. Production of reactive oxygen species (ROS) and activation of the calpain system and the NOD-like receptor protein 3 (NLRP3) inflammasome are closely related to the pathogenesis of depression. However, the relationships among those pathways and the protective effects of PSP have not been characterized. In this study, lipopolysaccharide (LPS) and chronic unpredictable mild stress- (CUMS-) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…These changes in monosaccharide content after steaming might explain the enhanced biological activity. Additionally, in a previous study we analyzed the monosaccharide composition of non-steamed PSP by UHPLC [ 18 ], and our findings were consistent with the literature. Therefore, we did not repeat this part of experiment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These changes in monosaccharide content after steaming might explain the enhanced biological activity. Additionally, in a previous study we analyzed the monosaccharide composition of non-steamed PSP by UHPLC [ 18 ], and our findings were consistent with the literature. Therefore, we did not repeat this part of experiment.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Li et al have pointed out that the structural properties and antioxidant activity of PSP change after steaming [ 17 ]. Our previous studies have shown that PSP can ameliorate inflammation and relieve oxidative stress to prevent depression-like behaviors in mice [ 18 , 19 ]. However, the effect of steaming on the biochemical activity of PSP against memory impairment has not been studied, and its mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In mice with lung injury, raw and honey-processed PCP could increase levels of SOD, inhibit pulmonary inflammation through the NF-κB pathway, and reduce the occurrence of pulmonary oxidative stress via the AMPK-Nrf2 pathway [ 133 ]. The protective effect in lung injury may be tightly related to the antioxidant and anti-inflammatory activities of PCP [ 134 , 135 ].…”
Section: Applications For Health-promoting Activitiesmentioning
confidence: 99%
“…PCP exerted antidepressant effects by regulating the oxidative stress-calpain-1- NOD-like receptor protein 3 (NLRP3) signaling axis. PCP prevented chronic unpredictable mild stress-induced changes in the calpain system and reduced depression-like behavior [ 84 ]. Moreover, methanol extract from P. odoratum administration reversed intestinal microbiota compositions, inhibiting H 2 S-related bacteria, a lower level of H 2 S, and higher content of short-chain fatty acid-related bacteria [ 85 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%